2014
DOI: 10.1080/15402002.2013.845783
|View full text |Cite
|
Sign up to set email alerts
|

The Course and Character of Sleepwalking in Adulthood: A Clinical and Polysomnographic Study

Abstract: To describe characteristics of adult sleepwalking (potential triggers and correlates with polysomnography), 52 patients were interviewed regarding their sleepwalking episodes and underwent video-polysomnography on two consecutive nights. Sleepwalking history averaged 12 years and frequent episodes (more than once per week) occurred in 62%. Higher frequency was associated with earlier onset of sleepwalking (p < 0.005) and 53.8% reported dangerous sleepwalking behavior. The most common self-reported triggers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…Stress was mentioned by almost two-thirds of them and sleep deprivation, anxiety and alcohol consumption were also frequently reported. Interestingly, full moon was reported by 25% of our patients as a trigger factor, suggesting a periodic occurrence of the episodes, whereas in previous studies, it was rarely mentioned [9] or not mentioned at all. In our cohort, as in previous studies [18, 19], there were more males among sleepwalkers.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Stress was mentioned by almost two-thirds of them and sleep deprivation, anxiety and alcohol consumption were also frequently reported. Interestingly, full moon was reported by 25% of our patients as a trigger factor, suggesting a periodic occurrence of the episodes, whereas in previous studies, it was rarely mentioned [9] or not mentioned at all. In our cohort, as in previous studies [18, 19], there were more males among sleepwalkers.…”
Section: Discussionmentioning
confidence: 56%
“…Lopez et al [7] reported that subjects with late-onset (subjects older than 9 years) primary SW (subjects with comorbidities were excluded) had lower incidence of violent behaviours and were more prone to worsening of their SW over time compared to those with early-onset SW [7]. However, in another cohort, Bušková et al[9] found no association between age at onset of SW with violent and injurious behaviour.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Sleepwalkers are difficult to be awakened and there is usually no recall of the episodes. Self-injuries [63,64] and rarely even homicidal, filicidal, and suicidal episodes are possible [65]. Sleepwalkers have a higher frequency of other parasomnias (sleep terrors, confusional arousals, enuresis, sleeptalking, bruxism), nocturnal eating (somnophagia), and abnormal sexual behavior during sleep [66].…”
Section: Sleepwalking (Somnambulism)mentioning
confidence: 99%